Comparison between ultrasound guided femoral 3 in 1 block versus blind fascia iliaca compartment block as analgesia prior positioning for spinal anaesthesia - Rubi, Ikhwan Wan Mohd (2016)
Introduction: Femur bone fracture may cause considerable amount of pain and peripheral nerve block has been advocated for use in this condition. Many techniques have been described to ease the pain in this kind of patient either prehospital and postoperative setting. However, it remains underutilised and not routinely done. Most of the time, patient either given intravenous analgesic or no analgesic. Objectives: This study aimed to evaluate the efficacy of ultrasound guided femoral 3 in 1 block versus the blind technique single shot fascia iliaca compartment block as an analgesia method in patients prior positioning for spinal anaesthesia in femur fracture surgery. Patients and Methods: This study was a prospective, single blinded and randomized controlled trial. A total of 60 patients aged between 18 to 65 years old consisted of ASA I to III were included in this study. Patients were divided into two groups by using computer assisted randomization. Group A received single shot blind fascia iliaca compartment block whereas group B received ultrasound guided femoral 3 in 1 block. The pain score at rest, upon movement and at interval of 5-10 minutes after block performed were recorded using Visual Analog Score (VAS). Results: Ultrasound guided femoral 3 in 1 block provides faster reduction of VAS at least 5 minutes’ post block and significant VAS reduction at 20 minutes’ post block. Less intravenous fentanyl required for rescue analgesia in femoral 3 in 1 block group. However, both blocks were comparable in term of reduction of VAS at 30 minutes’ post block. Conclusion: Femoral 3 in 1 block provides significantly faster relief of pain in femoral bone fracture. However, after 30 minutes’ total pain reduction in both techniques are similar. Both are equally effective and safe.